Seasonal Variation in the Biological Traits of Invasive Amazon Sailfin Catfish (Pterygoplichthys pardalis) in East Kolkata Wetlands, India - HUSSAN, AJMAL; NAIK, AT RAMACHANDRA; ADHIKARI, SUBHENDU; DAS, ARABINDA; HOQUE, FARHANA; SUNDARAY, JITENDRA KUMAR (Journal of the Indian Society of Coastal Agricultural Research, 2024)
Invading sailfin catfish Pterygoplichthys spp. in East Kolkata Wetlands (EKW), India were studied for their length-weight relationship (LWR), condition factor and reproductive characteristics covering pre-monsoon, monsoon and post-monsoon seasons. Using seine nets, fish samples were taken every month from May to December 2022 from five distinct EKW sites. Season-specific b-values for the LWR showed negative allometric growth, ranging from 2.663 to 2.809. Seasonal variation was negligible for Fulton’s condition factor (Kc), which varied between 0.741 and 0.756. The mean relative condition factor (Kn) was likewise found to be near 1 in all seasons (0.999 - 1.041). The sex ratio (male to female) showed an average mean value of 1: 3.61, with no noticeable seasonal change. However, gonado-somatic index (GSI) of males (0.164±0.007) and females (7.174±0.225) during the monsoon months (July - September) was found to be considerably greater (p <0.001) than pre-monsoon and post-monsoon GSI of the respective gender. Females were observed to have a lower mean total length at maturity (31.6 - 35.3 cm) than males (36.2 - 37.1 cm). No significant difference in mean absolute fecundity (3914.63±103.70 nos. female-1) of ripe females was observed, although gonad mass and relative fecundity (RF) differed considerably (p <0.05) by season. Seasonal interactions with study sites were found to have a considerable impact on ripe females’ RF and egg size, as well as Kn and GSI of both sexes. It was also noted that the condition factors and reproductive characteristics of sailfin catfish varied each month. Overall, mean Kn values of close to 1 ( 1) indicate that sailfin catfishes in EKW are in excellent condition of health and well-being. Additionally, the mean GSI of mature females was found continuously greater than three (>3) in each month of the study period, indicating that these fishes in EKW had a protracted breeding time.